2005
DOI: 10.1016/j.febslet.2005.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of protein subcellular location using a combined feature of sequence

Abstract: To understand the structure and function of a protein, an important task is to know where it occurs in the cell. Thus, a computational method for properly predicting the subcellular location of proteins would be significant in interpreting the original data produced by the large-scale genome sequencing projects. The present work tries to explore an effective method for extracting features from protein primary sequence and find a novel measurement of similarity among proteins for classifying a protein to its pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 52 publications
(57 reference statements)
0
33
0
Order By: Relevance
“…The comparison results demonstrate that all the testing methods can provide a better prediction performance for each class. Our studies also indicated that the jackknife test can provide a bias-free estimate of the accuracy at a much-reduced computational cost, which is an acceptable test for evaluating the performance of a prediction approach [24,28].…”
Section: Comparisons With Different Testing Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…The comparison results demonstrate that all the testing methods can provide a better prediction performance for each class. Our studies also indicated that the jackknife test can provide a bias-free estimate of the accuracy at a much-reduced computational cost, which is an acceptable test for evaluating the performance of a prediction approach [24,28].…”
Section: Comparisons With Different Testing Methodsmentioning
confidence: 66%
“…Thus, it is reasonable that kernel method combined with other properties (e.g. structural properties) of the amino acid residues will improve the prediction performance [28].…”
Section: Comparisons With Different Methodsmentioning
confidence: 99%
“…[82] [b] Based on a SVM model of residue-couple. [85] [c] Based on a 1-NN model of dipeptide composition. [85] FULL PAPER WWW.Q-CHEM.ORG…”
Section: Discussionmentioning
confidence: 99%
“…[82] [b] Based on a SVM model of residue-couple. [85] [c] Based on a k-NN model of complexity information. [84] FULL PAPER WWW.Q-CHEM.ORG As shown in Table 9, our approach achieved an overall accuracy of 87.7% for eukaryotic proteins.…”
Section: Comparison With Existing Methodsmentioning
confidence: 99%
See 1 more Smart Citation